Thermal Spray 1998: Proceedings From the International Thermal Spray Conference 1998
DOI: 10.31399/asm.cp.itsc1998p1149
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Thermal Spraying of Silicon Nitride-Based Powders

Abstract: Thermal spraying of silicon nitride has been considered impossible because the high temperatures of the spray processes lead to its decomposition and oxidation. To suppress the degradation oxide bonded silicon nitride spray powders (OBSN) have been developed. In this paper spray experiments with these powders by detonation gun spraying (DGS) and atmospheric plasma spraying (APS) with axial powder injection are described. All coatings were characterized using optical microscopy and X-ray diffraction. In additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…The plasma at the arc initiating point then receives an electromagnetic force pulse and forms an electromagnetically accelerated plasma of the working gas that heats and propels the powder particles with supersonic speed towards the substrate (Figure 3d,e). adhering coatings with high silicon nitride contents [46,47]. In addition, the optimization of heat transfer into powder particles to control the critical viscosity of the oxide binder phase was found to be one of the most decisive factors [48] that requires sophisticated powder preparation procedures [49].…”
Section: Silicon Nitride Coatingsmentioning
confidence: 99%
See 3 more Smart Citations
“…The plasma at the arc initiating point then receives an electromagnetic force pulse and forms an electromagnetically accelerated plasma of the working gas that heats and propels the powder particles with supersonic speed towards the substrate (Figure 3d,e). adhering coatings with high silicon nitride contents [46,47]. In addition, the optimization of heat transfer into powder particles to control the critical viscosity of the oxide binder phase was found to be one of the most decisive factors [48] that requires sophisticated powder preparation procedures [49].…”
Section: Silicon Nitride Coatingsmentioning
confidence: 99%
“…The coating consists prominently of α-Si3N4, minor amounts of ß-Si3N4, and traces of YAG and SiAlONs with different degrees of substitution 1 < z < 4, predominately z = 1. The powders used for detonation and EMAP spraying were synthesized by mixing commercial α-Si3N4 powder with oxidic sintering aids such as alumina and yttria, agglomerated by spray drying using an organic binder and subsequently sintered at 1450 • C in a nitrogen atmosphere [46,51]. The powders used for detonation (Figure 4A) and EMAP spraying (Figure 4B) contained 68 mass% Si3N4 + 16 mass% Al2O3 + 16 mass%, whereby the volume of the oxidic binder phase comprised 30%.…”
Section: Silicon Nitride Coatingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Further efforts to improve the coating quality were made using detonation gun spraying and axial powder injection atmospheric plasma spraying, but the decomposition of the silicon nitride phase presented another problem. 9 Research has been reported on spraying a mixed powder of silicon nitride with crushed soda-lime glass but again the quality of the coating microstructure and properties were limited. 10 This research will use a low temperature borosilicate glass as a binder to produce silicon nitride-glass composite as feedstock for thermal spraying.…”
Section: Introductionmentioning
confidence: 99%